Optoelectronic microfluidic device for point-of-care blood plasma viscosity measurement - Bakhtiaridoost, Somayyeh; Musuroi, Cristian; Volmer, Marius; Florescu, Monica (Lab on a chip, 2024)
Physical properties of blood plasma, such as viscosity, serve as crucial indicators of disease. The inherent capillary effect of paper microchannels, coupled with minimal sample requirement, stimulated the advancement of paper-based viscometers. This study presents a precise, non-contact optoelectronic system using a microfluidic platform for the measurement of blood plasma viscosity. Microchannels were defined onto the filter paper using an available and inexpensive wax crayon, without the need for conventional wax printing equipment. The time required for the 5 μL sample to pass a specific distance was measured using two pairs of infrared sensors. Subsequently, this data was sent to the microcontroller, which automatically calculated the viscosity. Throughout the measurements, sample temperature was maintained at a constant 37 °C through an integrated heater with automated control. The microfluidic platform successfully processed real samples, yielding viscosity measurements in under three minutes. Evaluation with fetal bovine serum, spiked with varying protein concentrations in both native and denatured states, demonstrated a precision exceeding 96% compared to conventional Ostwald viscometer readings. For human subjects exhibiting pathologies affecting serum and plasma viscosity compared to physiological norms, strong correlations were observed between resultant values and clinical diagnoses. The proposed device aims to replace expensive and complex optical equipment, offering a safer alternative for measuring plasma viscosity. Unlike similar devices, it eliminates the risk of component deformation due to chemical contact or unsafe irradiation. Non-contact, highly accurate and fully automated measurement of the blood plasma viscosity using the optical transparency technique at a constant temperature of 37 °C.